Understanding the epidemiology of human salmonellosis - Aung Kyaw Thu (Nanyang Technological University, 2021)
Salmonella is an important foodborne pathogen. It is commonly transmitted through the consumption of contaminated food, and infrequently through other modes such as person-to-person contact and contacts with companion animal and wildlife reservoirs. Salmonella enterica represents the most pathogenic species. There are >2,600 serovars identified with some showing restricted host selectivity, while the vast majority of serovars have a broad host spectrum and pose public health risks. Besides its ability to cause illness in humans, the emergence of antimicrobial-resistant Salmonella has been reported, threatening public health and food safety, around the world. In Singapore, the incidence of salmonellosis has been on the rise, since it has been denoted as a mandatory notifiable disease in 2008. Identification of the important risk factors associated with infection is essential to reduce the burden of salmonellosis. This study takes a multipronged approach which aims to determine the distribution and characteristics of Salmonella in humans and food, so as to identify important risk factors associated with these infections. Using a One Health approach, the study has offered insights into the epidemiology of Salmonella, which is used to inform future risk assessment and public health measures.